Analisis E. Coli Pada Air Minum Dalam Kemasan Yang Beredar Di Kota Tasikmalaya - Meylani, Vita; Putra, Rinaldi Rizal (Bioeksperimen: Jurnal Penelitian Biologi, 2019)
Drinking water is the main need of humans as living things. Over time, humans are more practical so that for drinking needs they prefer to use bottled drinking water or refill drinking water. The high demand for bottled water raises the number of drinking water companies that issue bottled drinking water products. However, the quality of bottled water still needs to be assessed because it is not through pasteurization or other processing. So the microbiological content remains to be investigated. This study aimed to determine the bacteriological content in bottled drinking water. This study uses the Most Probable Number (MPN) method to test its bacterial content and gamma ray radiation to test its radiosensitivity. The sample in this study was bottled drinking water of various brands circulating in the City of Tasikmalaya. Based on the research results obtained from 13 samples there is 1 sample containing E. coli which is code B1 with a total bacterial content of 7 cells per 100 ml. So it can be concluded L samples are known to contain E. coli as much as 1.9 x 105 cells per ml.